Functional Nanomedicines for Targeted Therapy of Bladder Cancer - Tang, Chao; Liu, Heng; Fan, Yanpeng; He, Jiahao; Li, Fuqiu; Wang, Jin; Hou, Yuchuan (Frontiers in Pharmacology, 2021)
Bladder cancer is one of most common malignant urinary tract tumor types with high incidence worldwide. In general, transurethral resection of non-muscle-invasive bladder cancer followed by intravesical instillation of chemotherapy is the standard treatment approach to minimize recurrence and delay progression of bladder cancer. However, conventional intravesical chemotherapy lacks selectivity for tumor tissues and the concentration of drug is reduced with the excretion of urine, leading to frequent administration and heavy local irritation symptoms. While nanomedicines can overcome all the above shortcomings and adhere to the surface of bladder tumors for a long time, and continuously and efficiently release drugs to bladder cancers. The rapid advances in targeted therapy have led to significant improvements in drug efficacy and precision of targeted drug delivery to eradicate tumor cells, with reduced side-effects. This review summarizes the different available nano-systems of targeted drug delivery to bladder cancer tissues. The challenges and prospects of targeted therapy for bladder cancer are additionally discussed.